History of madness - Foucault, Michel 1926-1984 (Routledge, 2006)
Challenging entrenched views of madness and reason, History of Madness is one of the classics of 20th century thought. It is Foucaultʼs first major work, written in a dazzling and sometimes enigmatic literary style. It also introduces many of the inspiring and radical themes that he was to write about throughout his life, above all the nature of power and social exclusion. History of Madness begins in the Middle Ages with vivid descriptions of the exclusion and confinement of lepers. Why Foucault asks, when the leper houses were emptied at the end of the Middle Ages, were they turned into places of confinement for the mad? Why, within the space of several months in 1656, was one out of every hundred people in Paris confined? Foucaultʼs bold and controversial answer is that throughout modern history, madness has meant isolation, repression and exclusion. Even the Enlightenment, which attempted to educate and include the mad, ended up imprisoning them in a moral world. As Foucault famously declared to a reporter from Le Monde in 1961, ʺMadness exists only in society. It does not exist outside the forms of sensibility that isolate it, and the form of repulsion that expel it or capture it.ʺ Shifting brilliantly from Descartes and early Enlightenment thought to the founding of the Hopital General in Paris and the work of philanthropists and early psychiatrists such as Philippe Pinel and Samuel Tuke, Foucault focuses throughout not only on the philosophical and cultural values attached to the mad. He also urges us to recognize the creative forces that madness represents, drawing on examples from Goya, Nietzsche, Van Gogh and Artaud. History of Madness is an inspiring and classic work that challenges up to understand madness, reason and power and the forces that shape them. Also includes information on alienation, animal spirits, asylums, Hieronymus Bosch, brain, burning at the stake, Christ and symbolism, classical age, confinement, convulsions, crime, delirium, dementia, dreams, alienation and exclusion, fear, God, hallucinations, hospitals, houses of confinement, houses of correction, hysteria, the insane, lunatics, mania, melancholy, mind, morality, positivism, prisons, poverty, punishment, the Renaissance, the French Revolution, sin, soul, suicide, symbolism, treatments, vapours, venereal disease, water, wisdom, witchcraft, women, work, workhouses, etc.